PENGARUH UKURAN PERUSAHAAN DAN PENERIMAAN OPINI GOING CONCERN TERHADAP HARGA SAHAM - Siregar, Hesekiel; Nurmala, Putri (Jurnal Riset Keuangan dan Akuntansi, 2018)
This study aims to determine the effect of firm size and acceptance of a going concern opinion on stock prices. In this study, the object of which is manufacturing firms listed in Indonesia Stock Exchange (BEI) in the consumer goods sector to the period from 2011 until 2015. In this study, the data used is data based on annual financial reports obtained through the site www .idx.co.id and sahamm price report data obtained through www.sahamok.com site. The sampling method this study using purposive sampling counted 17 manufacturing companies in the consumer goods sector for 5 years for a total observation in this study to 85 data. Statistical calculations used to test the hypothesis in this study is the associative analysis and verification analysis. Analysis consisted of deskriktif statistical verification, classic assumption test, multiple linear regression analysis, analysis of determination, f test, t test. The results of this research shows that the size of the companies have a significant effect on stock prices and the acceptance of a going concern opinion does not affect the stock price.Â Key Words: Company Size, Acceptance of Going concern Opinion, Stock Price